Tender prices in local bus transport in Germany - an application of alternative regression techniques - Arne Beck; Matthias Walter (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2010)
Competitive tendering of local bus services in Germany has received increased attention. Employing Seemingly Unrelated Regression analyses, we observe that prices have regionally varying determinants; for example, while prices throughout most of the federal state of Hesse increase over time, prices in the Munich area decrease. Optimisation of bus utilisation in general has a cost-decreasing impact, confirming that public transport authorities can reduce prices via adequate transport planning. Furthermore, Stochastic Frontier Analysis shows that tender prices in Hesse are slightly less efficient. Moreover we conclude that the public transport authority's experience has an efficiency-increasing impact which supports the introduction of overarching authorities.
urn:nbn:de:swb:90-211931
Keywords: C12; C13; C31; H57; K23; L16; L92; R32; R48; 330; public transport; bus; tendering; price; region; SUR analysis; SFA; Ausschreibung; Omnibusverkehr; Öffentlicher Personennahverkehr; Fahrpreis; Technische Effizienz; Schätzung; Deutschland